Anti-Crisis Solutions for Regional Energy Sector - Gitelman, Leonid Davidovich; Bokarev, Boris Aleksandrovich; Gavrilova, T.B.; Kozhevnikov, Mikhail Viktorovich (Economy of Regions, 2015)
The paper considers anti-crisis solutions for the electricity sector that fall into the category of strategic ones. Their primary purpose is to ensure the flexibility and adaptability of the system and prevent emergencies in the future. The authors explain the need for a holistic approach to taking anti-crisis decisions in power engineering and propose ways to improve the economic mechanism of cost reduction based upon international practice and placed in the Russian context. The benefits of demand-side management in ensuring the reliability of power supplies amid crisis are shown. The paper looks at various implementation modalities for demand- side management programmes and explores development prospects for distributed generation in Russia and stand-alone power supply options for manufacturing companies. Factors are assessed that affect the cost effectiveness of going off the grid. A general scheme of cost management aimed at reaching the strategic goals of the regional electricity sector is presented. The authors reveal possible applications and advantages of using predictive analytics for effective cost management. Ways of improving asset management are considered as well as the possibility of their employment in the Russian context. The key barriers to their implementations and ways of overcoming them are identified.